Examination of the attitudes of prospective teachers toward the history of Turkish education course according to different variables - Dilsat Peker Ünal; Mehmet Sağlam; Berkay Kılıç (Turkish History Education Journal)
The History of Turkish Education (HTE) course is a course designed to present the transformation of the Turkish education system based on social, economic, and political changes for prospective teachers and ensure that prospective teachers interpret the present and the future accurately by understanding the past. As in other courses, it is needed to identify various qualities such as attitudes toward the HTE course, self-efficacy, interests, and beliefs and keep these qualities in mind during the conduct of the course. These qualities will increase efficiency in the learning and teaching process. This study aimed to investigate attitudes toward the HTE course, which is offered at faculties of education, according to different variables. The correlational method, which is a quantitative research method, was used in the study. The sample of the study consisted of 363 prospective teachers receiving education at various departments and various class levels at the education faculty of a state university in the 2022-2023 academic year. To identify the attitudes of the participants toward the HTE course, a personal information form prepared by the researchers, the “Attitude Scale regarding the History of Turkish Education Course”, and the “Maggie McVay Lynch Learning Style Inventory” were used. Frequencies, percentages, mean values, independent-samples t-test, one-way analysis of variance (ANOVA), and post hoc tests were used in the analyses of the collected data. According to the results of the study in general, prospective teachers had above-average positive attitudes toward the HTE course, their attitudes toward the course did not differ significantly based on gender, department, class year, or grade point average, but they differed based on their learning styles. The obtained results were discussed alongside the results of previous studies, and various recommendations were proposed.